The Creative Procces of Writing a Film Series “Aku Pemuda” - Budi Dwi Arifianto; Erny Kurnia Damayanti (Jogjakarta Communication Conference (JCC), 2023)
This study aims to find out how the creative process of writing scripts for the film series "Aku Pemuda". The creative process is the process of finding ideas and relating them to facts. The script is important because it is a reference for the Director and Production Team in carrying out the production process. Writers are required to have high creativity in developing story ideas to create quality scripts because this is one of the creative processes. The method used in this study is a case study. The purpose of this study is to find out how the creative process of the author in developing story ideas become a complete film script. The technique for collecting data in this study is interviewing the author. The technique for collecting data at the stage of writing the script, there are several stages that the writer must go through, namely, writing the title, researching, brainstorming, building a plot, outlining, developing, first draft, rewriting, protecting, sell. this study is interviewing the author. The stages of script writing that each writer will go through are different. The results of this study show that the writer develops story ideas that have been given by the client and the writer does not go through all stages of script writing but, there are several stages of script writing that the writer went through such as the author's research in determining the character, determining the title, and brainstorming involving the production team and the MUSPADA client.